OP0051 The activating patients at risk for osteoporosis study: a randomized trial within the global longitudinal study of osteoporosis in women cohort. (15th June 2017) - Danila, M; Anderson, F; Greenspan, S; LaCroix, A; Nieves, J; Silverman, S; Watts, N; Curtis, J; Saag, K
Abstract : Background: Osteoporosis treatment rates are declining, even among those with past fractures. Novel, low cost approaches engaging and activating patients are needed to improve care. Objectives: To test a multi-modal, tailored, direct-to-patient, behavioral, video intervention aimed at improving rates of osteoporosis medication use. Methods: We conducted a controlled, randomized clinical trial of our novel intervention among US women in the Global Longitudinal Study of Osteoporosis in Women cohort with self-reported fracture history who were not currently using osteoporosis therapy. The primary outcome at 6-months was self-report of osteoporosis medication use. Secondary and exploratory outcomes included starting calcium and vitamin D, bone mineral density (BMD) testing, readiness for behavioral change, and barriers to treatment. Results: We randomized 2684 women to receive the intervention materials or usual care. Study participants were 92.6% Caucasian, with a mean (SD) age 74.9 (8.0) years, and a self-reported lower than average risk for osteoporosis (40.0%). In the 12 months prior to randomization, 1390 women reported talking with their doctor regarding osteoporosis, 7.4% reported a fracture, vitamin D or calcium supplementation were reported as 83.5% and 68.6%, respectively. We observed no differences in sociodemographic characteristics and no significant differences in the primary (11.7% vs 11.4%) and secondary (calcium, 31.8% vs 32.6%; vitamin D, 41.3% vs 41.9%; bone density, 61.8% vs 57.1%) end points between the intervention and usual care groups. Exploratory post-hoc analyses demonstrated that women in the intervention arm had more favorable views towards osteoporosis medications compared with the usual care arm and a lower proportion were in the unaware and uninvolved stages of behavior change regarding osteoporosis medications (OR=1.57, CI[1.11, 2.23]). We found that barriers to treatment were higher in the intervention, as compared to usual care arm at 6 months: concerns regarding osteonecrosis of the jaw (OR=1.58[1.14, 2.18]). We found significant differences in self-report BMD testing among the subgroup of women with no history of osteoporosis medication use (OR=1.30 [1.01, 1.66]), among those who provided a contact phone number or email address (OR=1.33 [1.01, 1.74]), and among those who did not report past BMD testing on the baseline survey (OR=1.53 [1.40, 1.68]) (Figure A). The proportion of self-reported osteoporosis treatment was similar between those with appreciable exposure to the online intervention compared with the control group (adjusted OR=1.22 [0.73, 2.04]) (Figure B). Conclusions: This randomized study testing a novel, personalized educational intervention, did not increase the use of osteoporosis therapy at 6 months. The intervention appeared to have influenced participants' readiness for behavior change. Acknowledgements: National Institute of Arthritis and Musculoskeletal and Skin Diseases R01 AR060240 (KS) and K23 AR062100 (MD). Disclosure of Interest: M. Danila: None declared, F. Anderson Consultant for: Millennium Pharmaceuticals, S. Greenspan Grant/research support from: Amgen, Lilly, Consultant for: Merck, A. LaCroix Consultant for: Amgen, Pfizer, Sermonix, J. Nieves: None declared, S. Silverman Grant/research support from: Amgen, Lilly, Consultant for: Amgen, N. Watts Shareholder of: OsteoDynamics, Grant/research support from: Shire, Consultant for: AbbVie, Amgen, Janssen, Merck, Radius, Sanofi, Paid instructor for: Amgen, Shire, J. Curtis Grant/research support from: Amgen, Consultant for: Amgen, K. Saag Grant/research support from: Amgen, Lilly, Merck, Consultant for: Amgen, Lilly, Merck